DEVELOPMENT OF COBALT OXIDE AND HIERARCHICALLY POROUS ACTIVATED CARBON COMPOSITES FOR MICROWAVE ABSORPTION AT XBAND FREQUENCY - YUSUF, JEMILAT YETUNDE (2021)
Electromagnetic interference (EMI) affects the proper functioning of electronic devices due to the advances in electronic devices, and excessive exposure to EM radiation endangers human health. Microwave absorption has emerged as an innovative application area where nanomaterials can tackle EMI due to their intrinsic dielectric and magnetic properties. Thus, this study involves fabricating novel microwave absorbing materials (MAMs) from Co3O4 and porous activated carbon (PAC) obtained from banana peel. In this study, porous activated carbon (PAC) was derived from banana peel via chemical activation and carbonization at different temperatures. Then, Spinel cobalt oxide (Co3O4) nanoparticles and Co3O4@PAC composites were prepared using the facile hydrothermal method. The samples' thermal stability, phase crystallinity, chemical composition, surface morphology, and porosity were studied using TGA, XRD, FTIR, XPS, FESEM, and SAP characterization techniques, respectively. The FESEM result reveals the formation of a unique cornale like flower structure. The samples' microwave absorption properties (MAP) at 30 wt% loadings were studied at X band (8.2 - 12.4GHz) frequency. A Co3O4@PAC700 composites display enhanced microwave absorption performance with a minimum RL value of - 44.50dB at 10.84 GHz with an adequate absorption bandwidth of 1.08 GHz at 2.0 mm absorber thickness. The unique flower-like morphology of the composites with good porosity would favour EM wave scattering and multiple reflections of EM wave, thereby resulting in high attenuation of the EM wave. The flower-like morphology prolongs the electromagnetic wave propagation path, favoring gradual attenuation of electromagnetic waves. This work suggests that the Co3O4@PAC composites can be considered a good absorber for EM absorption application. This study provides a new path to designing novel magnetic and dielectric composites for effective microwave absorption.